TI_GERICHTE 11.2009.183 vom 19. Dezember 2012 , Iscrizione ipoteca legale provvisoria degli artigiani e degli imprenditori - TI Tribunale d'appello (2012)
Iscrizione ipoteca legale provvisoria degli artigiani e degli imprenditori